The Legal Consequences For Buying Motor Vehicles Without Motor Vehicle Authorization Letter - Peter Jeremiah Setiawan; Shintya Yulfa Septiningrum; Xavier Nugraha (Syariah: Jurnal Hukum dan Pemikiran, 2021)
This legal research aims to determine the consequences of criminal law and civil law consequences for buyers who purchase motorized vehicles without complete and valid documents. This legal research is a normative juridical research. The nature of this legal research is an analytical description to describe an ongoing situation or situation as data for the object of research so that it can explore ideal things which can then be analyzed based on legal theory or applicable laws and regulations. Based on the results of research and discussion, the consequences of criminal law against buyers who purchase motorized vehicles without complete and valid documents are that Article 480 paragraph (1) of the Criminal Code on criminal acts of detention must be fulfilled with subjective and objective elements  Furthermore, the effect of civil law on buyers who purchase motorized vehicles without complete and valid documents is that it is possible for the owner of the motor vehicle to file a lawsuit against the law based on Article 1365 of the Civil Code.